The Impacts of Ramadan Intermittent Fasting on Saliva Flow-Rate and Metabolic Data: A Systematic Review - Besbes, Amira; Khemiss, Mehdi; Bragazzi, Nicola; Ben Saad, Helmi (Frontiers in Nutrition, 2022)
TThe aim of this systematic review was to report the impacts of Ramadan intermittent fasting (RIF) on salivary flow-rate (SFR) and metabolic parameters. A thorough literature search was carried out using the databases PubMed and Scopus from their inception up to July 15, 2021. The Boolean connectors used in PubMed were (Saliva [Mesh] AND Fasting [Mesh]). The same keywords were used in Scopus. Inclusion criteria were defined using PICOS. The research included all original studies involving “healthy” adults and published in English. Methodological quality assessment was performed utilizing the Joanna Briggs Institute Critical Appraisal Tool, which allows attributing scores from 1 to 11 to the selected studies. Two authors carried out the literature search, study selection, and data extraction. Differences on issues were resolved by a third author if necessary. The systematic review protocol was registered within the "Open Science Framework" (DOI 10.17605/OSF.IO/DE7BH). Six articles met the inclusion criteria. All studies were heterogeneous and had a high score of bias and several methodological differences. The following parameters were collected: SFR, melatonin, cortisol, glucose, immunoglobulin A (IgA), uric-acid, alkaline phosphatase (ALP), and aspartate aminotransferase (AST). The SFR decreased by 10% during Ramadan in fasting subjects. The circadian pattern of melatonin remained unchanged during Ramadan, but melatonin levels dropped significantly from baseline. The salivary cortisol levels were unchanged or increased during Ramadan. The salivary glucose levels were decreased. ALP increased significantly, whilst uric-acid and AST decreased significantly. Salivary IgA decreased during the last week of Ramadan. To conclude, there is a trend towards a decrease in SFR and the content of the majority of the biomarkers investigated, with the exception of ALP and uric-acid. These changes cannot be easily attributed to any single factor (hydration status, dietary habits, physical activity, or hygiene habits).